The Role of Speculative Trade in Market Efficiency: Evidence from a Betting Exchange - Brown, Alasdair; Yang, Fuyu (Review of Finance, 2017)
Abstract Does speculative trade reduce mispricing and help create efficient markets or does it drive prices further from fundamentals? We analyze betting exchange trading on 9,562 UK horse races in 2013 and 2014 to find out. Crucially, as each race is run, the fundamental value of bets is unambiguously revealed. We find that the volume of trade is predictive of fundamentals, suggesting that speculative trade is on average conducive to market efficiency. However, much of this effect is concentrated in the in-running period during races when, even without trade, asset fundamentals would be revealed seconds later.